Two-qubit state tomography using a joint dispersive readout. - Filipp, S; Maurer, P; Leek, P; Baur, M; Bianchetti, R; Fink, J; Göppl, M; Steffen, L; Gambetta, J; Blais, A; Wallraff, A (2009)
Quantum state tomography is an important tool in quantum information science for complete characterization of multiqubit states and their correlations. Here we report a method to perform a joint simultaneous readout of two superconducting qubits dispersively coupled to the same mode of a microwave transmission line resonator. The nonlinear dependence of the resonator transmission on the qubit state dependent cavity frequency allows us to extract the full two-qubit correlations without the need for single-shot readout of individual qubits. We employ standard tomographic techniques to reconstruct the density matrix of two-qubit quantum states.